The Effect of a Training Program using Prompting to Develop Receptive Language (Environmental Concepts) among a Sample of Children with Autism Spectrum Disorder - الرفاعي, عالية; آدم, بسماء; حسن , ريم (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The Effect of a Training Program using Prompting to Develop Receptive Language (Environmental Concepts) among a Sample of Children with Autism Spectrum Disorder